Incumbent Perempuan dalam Pemilihan Kepala Desa di Kabupaten Karangasem Tahun 2016-2022 (Jurnal Nawala Politika, 2023)
This research seeks to see how the trend of female Incumbents in Pilkades in Karangasem Regency forms a new structure in society where women have a high bargaining position in the village head election battle arena which is dominated by men. By using the Habitus approach from Pierre Bourdieu, the author sees that the capital of each agent, namely I Gusti Ayu Biksuni and Ni Putu Dewi Suryanti, was one of their successes in fighting in the Pilkades arena. The capital is; educational, social and cultural background, the Incumbent status of the two women, their activism during their tenure which went down to the community so that they became close to their citizens, then the supporting role which was also the parties in power in the election battle. Author found there was a positive trend related to the position of women in the political area in the village head order. Keywords: Incumbent, Women, Pilkades